Anesthetic-mediated cardioprotection: from molecular mechanisms to clinical translation challenges - Fu, Tingting; Jia, Xiao; Tang, Can; Yu, Dan; Zhou, Hui; Wang, Xinghe; Liu, Su; Wu, Kunwei (Frontiers in Physiology, 2025)
Anesthetics have long been recognized as essential pharmacological agents for surgical procedures, primarily valued for their ability to induce unconsciousness and provide analgesia. However, emerging research over the past 3 decades has revealed an additional and potentially transformative property of certain anesthetics: their ability to protect the heart against ischemic injury. This comprehensive review examines the cardioprotective effects of both intravenous and volatile anesthetics, with particular focus on propofol, ketamine, isoflurane, and sevoflurane. We analyze the molecular mechanisms underlying their protective actions, including modulation of mitochondrial function, reduction of oxidative stress, and regulation of key survival pathways such as PI3K/Akt/GSK3βand p53 signaling. The review evaluates preclinical evidence from cellular and animal models, as well as clinical studies investigating anesthetic-mediated cardioprotection in cardiac surgery patients. Special attention is given to the phenomenon of anesthetic preconditioning and postconditioning, their comparative efficacy, and the challenges in translating these protective strategies into clinical practice. We also discuss emerging concepts such as the role of microRNAs in mediating anesthetic-induced protection and the potential cardioprotective benefits of anesthetic combinations. Finally, we identify critical gaps in current knowledge and propose future research directions that may enhance the clinical application of anesthetic-mediated cardioprotection.